The Role of Sundanese Language Education in Developing Students' Politeness: A Study at Cikeusi II State Elementary School, Sumedang Regency - Dewi, Sahla Nur Aulia; Karim, Abdul; Asyiah, Nur (Journal of Innovation and Research in Primary Education, 2025)
Character education through regional language instruction has gained increasing attention as an effective approach to moral development. This study examined the role of Sundanese language education in developing students' politeness at Cikeusi II State Elementary School, Sumedang Regency, focusing on how linguistic instruction cultivates character values through cultural expressions and undak-usuk basa principles. A descriptive qualitative approach was employed involving one Sundanese language teacher and seventeen fifth-grade students aged 10-11 years who had participated in Sundanese language instruction for at least one academic year. Data were collected through structured classroom observations, semi-structured interviews with teachers and students, and documentation of learning materials. Thematic analysis was used to identify patterns related to politeness behaviors, teaching strategies, and implementation challenges, with triangulation ensuring data credibility. Sundanese language education demonstrated significant effectiveness in developing student politeness, achieving an 84.1% overall success rate across observed behaviors. Students showed highest proficiency in expressing gratitude (94.1%) and demonstrating respectful gestures (94.1%), while more complex hierarchical politeness behaviors such as avoiding interruptions with elders (76.5%) and careful word choice (70.6%) required continued reinforcement. Pedagogical approaches integrating role modeling, cultural storytelling, and contextual exercises proved effective, though limited instructional time, insufficient contextual media, and inconsistent family support posed implementation challenges. The findings support social learning theory and character education frameworks, demonstrating that regional language education serves as an effective vehicle for transmitting cultural values and developing moral behavior. However, inconsistencies between school and non-school environments highlight the need for comprehensive home-school-community collaboration to achieve sustainable character development outcomes.